Effect of arteriovenous fistula on cutaneous microvascular circulation in hemodialysis patients - Mabuchi, Hisao; Maruyama, Yoshifumi; Aoki, Tadashi; Kakiuchi, Takeshi; Nakahashi, Hisamitsu (Journal of Japanese Society for Dialysis Therapy, 1989)
Cutaneous microvascular blood flow (CMBF) was measured by laser Doppler flowmetry, to examine the effect of blood access (BA) on cutaneous microvascular circulation. We studied 10 normal subjects and 10 hemodialysis (HD) patients (male 3, female 7) who had arteriovenous shunt on the right or left forearm. Two patients showed luxurious perfusion. We made flow measurements in the center of the back of both hands in the resting supine position before and after HD, and 1 and 2 hours after HD started. 1) CMBF on the BA side (6.36-30.7ml/min/100cc) was markedly higher than on the non-BA side (1.62-4.21ml/min/100cc) in 4 patients, including 2 with swollen hands. This increased flow gradually decreased during HD, but 3 of the 4 patients showed transient elevation 1 hour after HD started. Of these 4 patients, the CMBF after HD on the BA side in the 2 patents with swollen hands were 3.3 and 7.3 times greater than on the non-BA side, but in the other 2 patients, they were 1.4 and 1.7 times. 2) The CMBF before HD in the remaining 6 patients ranged from 3.09-5.30ml/min/100cc on the non-BA side and 1.57-5.05ml/min/100cc on the non-BA side, and it did not change during HD. 3) There was no significant difference in CMBF on the non-BA side between the patients and normal subjects (1.10-4.34ml/min/100cc), and no correlation between CMBF and peripheral venous hematocrit. It is suggested that the increase in CMBF on the BA side depends on the massive inflow of arterial blood through the BA, and the measurement of CMBF is useful for the treatment and prevention of Iuxurious perfusion induced by BA.